Survey: mobile sensor networks for target searching and tracking. Issue 2 (3rd April 2018) - Albert, Anders; Imsland, Lars
Abstract: Mobile sensor networks can be employed in multiple applications, such as search and rescue, border patrol, battle scenarios and environmental monitoring. In this survey, we review the literature utilising mobile sensor networks in applications classified as target searching and/or tracking. Our contribution is threefold. First, we focus on the diverse types of filters applied to estimating the state of the targets. Second, we present the most common approaches to high-level trajectory planning for the sensors in the network to do target searching and/or tracking. Finally, we classify the literature based on the problem formulation used and solution characteristics. At the end of the survey, we discuss the current state of the literature and possible directions for future research efforts.